PH-sensitive carboxymethyl chitosan hydrogels via acid-labile ortho ester linkage as an implantable drug delivery system. (1st December 2019) - Gao, Jialu; Xu, Yong; Zheng, Yan; Wang, Xin; Li, Shuting; Yan, Guoqing; Wang, Jun; Tang, Rupei
Graphical abstract: Highlights: Implantable pH-triggered hydrogels were prepared via ortho-ester crosslinkage. The physicochemical properties and degradation rate of hydrogels are controllable. Nanoparticles-encapsulated hydrogels could be implanted into tumors in any shape. Hydrogels were continuously degraded in mildly acidic environment of tumor tissues. Nanoparticles-encapsulated hydrogels showed the superior antitumor effect. Abstract: A series of pH-sensitive carboxymethyl chitosan (CMCS) hydrogels were prepared via ortho ester linkage. DOX-loaded gelatin nanoparticles with an average diameter of around 50 nm were incorporated into hydrogels to obtain hybrid hydrogels (DOX-NPs-Gel), which could be locally implanted into tumor site in any shape. The physicochemical and mechanical properties of these hydrogels could be easily controlled by adjusting the proportion of crosslinking agent. DOX-NPs-Gel showed the pH-dependent degradation and drug release, and only 29.9% of DOX was released within 144 h at pH 7.4, while the cumulative release reached 49.3% and 65% at pH 6.5 and 5.0, respectively. In vivo study demonstrated that the implanted DOX-NPs-Gel efficiently improved DOX accumulation in tumor site through continuously degradation in mildly acidic environment of tumor tissues, and the tumor volume at the end of experiment was only 81.53 mm 3, while tumor size reached to 229.22 mm 3 and 174.15 mm 3 after intravenous treatment with free DOX and DOX-NPs, respectively.